Proposta de ensino de função quadrática usando software Winplot - Silva, Henrique Lobato da (Universidade Federal do Tocantins, 2024)
This dissertation proposes an innovative approach to teaching quadratic functions to 9th grade stu- dents, using the Winplot software as a supplementary tool in the learning process of Mathematics. Through analyzing the coefficients of the quadratic function and utilizing algebraic, graphical, and calculation windows, it is possible to visualize the graph and comprehend important concepts related to the function. The objective of this work is to provide teachers with a teaching proposal for the second-degree polynomial function, using the software as a mediation instrument. This methodology aims to make the learning of abstract content more dynamic, allowing students to visualize functions through the manipulation of commands and develop a comprehensive understanding of the subject. The proposal includes the presentation of exercises that can be later applied in the classroom. Thus, this research aims to improve the teaching methodology of Mathematics for basic education teachers and verify if students are capable of learning the content in practice, arousing their interest and participation during classes.